Penggunaan Teknologi Tepat Guna Bagi Pengerajin Bawang Goreng di Kelurahan Palmerah, Jakarta Barat - Farida; Ariyanti, Silvi; Prabowo, Herry Agung; Husnur, Achmad (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
MSME activities are one of the methods so that regional creative products can be recognized and open up business opportunities for business actors in the regions. One of the problems of MSMEs is in the management or managerial sector, especially the operations function in the production sector. The business of making fried onions in Palmerah District, West Jakarta, still uses manual methods in all of its production processes, so the problem that arises is how to increase sufficient production capacity with good quality. The problem that needs attention is that drying is still done manually on paper so it requires a long process, the packaging uses plastic and rubber so that it doesn't last long with an unattractive shape. On the other hand, business owners have a great desire to increase production capacity in line with the increasing market demand for fried shallots with better quality and packaging. Therefore, community service activities are carried out to help solve this problem through the application of appropriate technology in the form of oil slicing machines and vacuum sealer devices and providing training.